2022
DOI: 10.1002/vms3.746
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of the mRNA abundances of clock genes and glucose transporters in the jejunum of weanling‐growing pigs

Abstract: Background: Whether abundance of glucose transporter mRNAs in the small intestine of pigs shows circadian rhythms and its regulation by clock genes was still unknown. Objectives:We examined whether the abundance of glucose transporters and clock genes mRNAs in the small intestine of pigs shows circadian rhythms.Methods: Twenty barrows (4 weeks old) were reared under 12 h bright and 12 h dark lighting conditions. During the 3-week feeding trial, pigs were allowed free access to feed. The abundances of the mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A detailed interaction of the expression of glucose transport vector with circadian and clock genes in the pig small intestine by Kinoshita Yuki et al the study showed the levels of GLUT-2 mRNA exhibit significant diurnal variation that is always stronger in rats with a healthy metabolism. It also demonstrated significant diurnal changes in glucokinase mRNA, with higher levels of glucokinase mRNA in the pancreas of 6-week-old Landrace × Large White cross-breeds rats than in Wistar rats [ 28 ]. This effect causes glucose phosphorylation capacity to synchronize with food intake, enhancing glucose-stimulated insulin secretion and preventing postprandial hyperglycemia.…”
Section: Basic Overview Of Glut-2mentioning
confidence: 99%
“…A detailed interaction of the expression of glucose transport vector with circadian and clock genes in the pig small intestine by Kinoshita Yuki et al the study showed the levels of GLUT-2 mRNA exhibit significant diurnal variation that is always stronger in rats with a healthy metabolism. It also demonstrated significant diurnal changes in glucokinase mRNA, with higher levels of glucokinase mRNA in the pancreas of 6-week-old Landrace × Large White cross-breeds rats than in Wistar rats [ 28 ]. This effect causes glucose phosphorylation capacity to synchronize with food intake, enhancing glucose-stimulated insulin secretion and preventing postprandial hyperglycemia.…”
Section: Basic Overview Of Glut-2mentioning
confidence: 99%